Survey on the prevalence of Listeria monocytogenes in Belgian artisanal cheeses - Amaury Gérard; Soundous El-Hajjaji; Els Van Coillie; Azeddine Bentaib; Georges Daube; Marianne Sindic (Biotechnologie, Agronomie, Société et Environnement, 2020)
Description of the subject. Cheese is a vector of Listeria monocytogenes. By default, European Commission imposes its absence in cheese before sales, but fixes pH and water activity thresholds below which it cannot grow.